Influence of music therapy on the improvement of perceived well-being indices in women with breast cancer undergoing hormonal treatment - Fernández-Company, José Fernando; Quintela-Fandino, Miguel; Sandes, Vikrampal; García-Rodríguez, María (Taylor & Francis Group, 2024)
Background: Although there are a growing number of studies investigating the benefits of music therapy interventions with patients diagnosed with cancer, few studies have taken an approach that specifically examines indices of perceived well-being in women with breast cancer. Overcoming these challenges can be an important step in the recovery process. Purpose: The purpose of our study was to know the positive influence of responsive music therapy through gong sounds, emitted live, on different areas of well-being of women with breast cancer. Methods: Four individual sessions of responsive music therapy with live gong sounds were conducted in which three women (M = 54; SD = 5.57) participated both in the music therapy program and in the completion of the Functional Assessment of Cancer Therapy – Breast (FACT-B) and a semi-structured interview with ad hoc designed questions about perception of qualitative aspects. Results: The results showed that the music therapy sessions significantly improved, p = .043 < 0.05, various domains of perceived well-being in women with breast cancer. Discussion: This article highlights several key benefits associated with music therapy and various indices of well-being in women with breast cancer, identifies the limitations of the study, and discusses the findings. It is considered necessary to replicate this practice in future studies that include a larger sample and age range over longer follow-up periods. Translation for Health Education Practice: The text highlights the importance of considering music therapy as a complementary intervention in comprehensive cancer care programs, which may be relevant to health educators when considering intervention and support approaches for cancer patients. Health education interventions targeting the enhancement of cancer patients’ well-being should incorporate music therapy techniques.
Keywords: music therapy; women; well-being indices; breast cancer; hormonal treatment